Enteroviral infection causing fatal myocarditis and subclinical myopathy. Issue 1 (1st January 2000) - Arbustini, E; Porcu, E; Bellini, O; Grasso, M; Pilotto, A; Dal Bello, B; Morbini, P; Diegoli, M; Gavazzi, A; Specchia, G; Tavazzi, L
Abstract : Enteroviral RNA detection in myocarditis and dilated cardiomyopathy is rare. Enteroviral particles and RNA have recently been identified in patient's skeletal muscle, suggesting that skeletal more than heart muscle hosts the virus in chronic infection. Enteroviral RNA and virus-like particles were found in the myocardium and in the skeletal muscle of two patients with fatal myocarditis: a 39 year old man who died five days after the onset of febrile flu; and a 49 year old woman, assisted for 50 days with a left ventricular assist device, who then died from cerebral haemorrhage. Automated sequencing, alignment, and sequence comparison confirmed the enteroviral origin of polymerase chain reaction products and excluded contamination. These findings agree with prior observations of enteroviral localisation in the skeletal muscle of patients with dilated cardiomyopathy, and further support the hypothesis that skeletal rather than heart muscle may host the virus and serve as a reservoir in cardiomyopathies related to chronic infection.